Simon and Schuster's Guide to mammals - Boitani, Luigi; Anderson, Sydney, 1927-; Bartoli, Stefania (New York : Simon & Schuster, 1983)
Translation of: Mammiferi. Describes 426 species worldwide, illustrated in color, and with over 1,200 drawings, maps, and symbols.
Includes index.
Translation of: Mammiferi.
Bibliography: p. [506].
Booklist.
School Library Journal.
Young Adult
Keywords: Mammals; Mammals